INVESTIGATING SOURCES OF PERIPHERAL SEROTONIN SYNTHESIS: IMPLICATIONS FOR REGULATING METABOLISM - Yabut, Julian (My University, 2020)
Obesity is a major risk factor for type 2 diabetes (T2D) and non-alcoholic fatty liver disease (NAFLD), and is attributed to excess energy intake in comparison to energy expenditure. Therapeutics that reduce energy intake in obesity have limited efficacy, with weight loss typically reaching less than 10% of initial body mass, leading to efforts to uncover new therapies that may increase energy expenditure. Unlike lipid-storing white adipose tissue, brown and beige adipose tissues undergo futile cycling, oxidizing lipids and carbohydrates thereby increasing energy expenditure. With obesity, the metabolic activity of brown and beige adipose tissue is reduced, suggesting that restoring adipose tissue thermogenesis may represent a new means to enhance energy expenditure. Previous studies in mice have shown that peripheral serotonin synthesis by the enzyme tryptophan hydroxylase 1 (Tph1) inhibits adipose tissue thermogenesis and contributes to the development of obesity, insulin resistance and NAFLD. However, the primary Tph1 expressing tissue(s) inhibiting adipose tissue futile cycling is not known. In this thesis, we genetically removed Tph1 in mast cells of mice and discovered that this elevated beige adipose tissue activity protecting mice from developing high-fat diet induced obesity, insulin resistance and NAFLD. In contrast to these findings, genetic deletion of Tph1 in adipocytes did not result in protection from obesity, suggesting that mast cells are the primary source of serotonin that inhibits white adipose tissue thermogenesis. Lastly, to determine the importance of adipose tissue thermogenesis in mediating the beneficial metabolic effects of reduced Tph1, mice were housed at thermoneutrality, blocking the requirement for adipose tissue thermogenesis. Under these conditions, mice lacking Tph1 had comparable brown and beige adipose tissue metabolic activity, energy expenditure and adiposity, however, surprisingly, were still protected from insulin resistance and NAFLD. The studies in this dissertation have discovered that mast cell Tph1 is critical for inhibiting adipose tissue thermogenesis and that serotonin plays an important role in promoting NAFLD, independently of its inhibitory effects on adipose tissue thermogenesis. Collectively, these findings further define the roles of serotonin in regulating whole-body energy metabolism, providing critical clues and mechanistic insights for potential therapies to mitigate metabolic diseases.
PhD Dissertation
Keywords: Obesity; Type 2 Diabetes; Non-alcoholic Fatty Liver Disease; Serotonin; Thermogenic Adipose Tissue; Mast Cells; Metabolism; Immunometabolism